2020
DOI: 10.3390/agriculture10110498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Priming with Potassium Nitrate on the Performance of Tomato

Abstract: The seed industry and farmers have challenges, which include the production of poor quality and non-certified tomato seed, which ultimately results in decreased crop production. The issue carefully demands pre-sowing treatments using exogenous chemical plant growth-promoting substances. Therefore, to mitigate the above-stated problem, a series of experiments were conducted to improve the quality of tomato seeds (two cultivars, i.e., “Sundar” and “Ahmar”) and to enhance the stand establishment, vigor, physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 29 publications
3
23
1
2
Order By: Relevance
“…Priming with KNO 3 improves seed germination, mineral composition, proline, amylase, and protein pattern [ 17 ]. It improves seedling establishment and vigor and has a remarkable role in the pre-sowing accomplishment of germination phases [ 18 ]. However, the detailed metabolic events induced by KNO 3 during the sprouting process are not quite understood.…”
Section: Introductionmentioning
confidence: 99%
“…Priming with KNO 3 improves seed germination, mineral composition, proline, amylase, and protein pattern [ 17 ]. It improves seedling establishment and vigor and has a remarkable role in the pre-sowing accomplishment of germination phases [ 18 ]. However, the detailed metabolic events induced by KNO 3 during the sprouting process are not quite understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, less water uptake resulted in significant decreases of K ions in the spinach leaves [8]. Exogenous application of KNO 3 as treatment can increase multiple physiological and biochemical mechanisms [16]. Additional KNO 3 increases the photosynthetic pigment contents, potassium content, and enhances plant growth and decreases sodium in moisture-stressed plants.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium nitrate, due to its nutritional value, in addition to acting as a salt, also has the property of a growth regulator, with a significant impact on plant mass [ 35 ]. Moaaz et al [ 24 ] confirmed that KNO 3 as a priming agent can significantly improve plant mass and growth. Moreover, a marked effect of these treatments in terms of vigor index was observed.…”
Section: Discussionmentioning
confidence: 99%
“…A significant effect of priming on the nutritional composition of radish was also noticed [ 23 ]. It has been previously confirmed that seed priming significantly helps plants to accelerate cell division, transport stored proteins, and accelerate seed germination [ 24 ].…”
Section: Introductionmentioning
confidence: 99%